Exploring checks and balances - Krasner, Barbara (Searchlight books. Getting into government., 2020)
Explores the history of the concept of the separation of governmental powers in the United States, and briefly describes each of the three governmental bodies, what each does, and how they work to balance each other. Includes color photographs, sources for further information, a glossary, and an index.